Complexity and interdisciplinarity in novel socioecological perspectives: political ecology of urban metabolism - Delgado Ramos, Gian Carlo (2015)
Considering the complexity that characterizes current socio-ecological crisis, this paper argues that analyses based on complex systems and interdisciplinary approaches are increasingly needed, which in turn appeal for the emergency of novel hybrid socioecological perspectives. Arguments in favor of encouraging the co-production of knowledge of participatory and reflexive nature are presented, followed by a discussion on the main desirable characteristics and prevailing pathologies of knowledge-exchange practices and, in fact, within knowledge production. The just said is then exemplified with the case of political ecology of urban metabolism, a hybrid knowledge frontline field. It is concluded that the convergence of interdisciplinary approaches is a key feature of robust co-production of hybrid knowledge practices (based on broad participatory processes); the later particularly useful for consensual decision-making, say around socioecological complex problems of today.